Experimental hypothyroidism increases apoptosis in dimethylbenzanthracene-induced mammary tumors - López Fontana, Constanza Matilde (2013)
Epidemiological and in vitro data have not provided conclusive evidence concerning the involvement of thyroid hormones (THs) on mammary carcinogenesis. We used an in vivo model to assess the relationship between THs, adipose tissue and breast cancer development. Female Sprague-Dawley rats were treated with a dose of 7,12-dimethylbenz(a)anthracene (15 mg/rat) at 55 days of age and were then divided into four experimental groups: hypothyroid rats (HypoT, 0.01% 6-N-propyl-2-thiouracil in drinking water), untreated control (EUT); hyperthyroid rats (HyperT, 0.25 mg/kg/day T4 s.c.) and vehicle-treated control rats. The latency of tumor appearance and the incidence and progression of tumors were determined. At sacrifice, blood samples were collected for hormone determinations and samples of tumor and mammary glands were obtained for immunohistological studies. HypoT rats had retarded growth and an increase in mammary fat. The latency was longer (p<0.0001), the incidence rate was lower (p<0.05) and tumor growth was slower in HypoT rats compared to EUT and HyperT rats. Mitotic index and PCNA immunostaining were similar in all groups. HypoT rats showed increased apoptosis (p<0.05) as evaluated by the apoptotic index and TUNEL staining. No differences in serum prolactin and progesterone were observed. However, circulating estradiol (E2) was significantly lower in HypoT and HyperT rats. Serum leptin levels were reduced in HypoT rats even though the abdominal fat mass was similar in all groups. To note, the leptin level was higher in HypoT rats that developed mammary tumors than the level in non-tumoral HypoT rats. In conclusion, hypothyroidism altered animal growth, breast morphology, body composition, leptin secretion and serum E2 enhancing apoptosis and, consequently, retarding mammary carcinogenesis in rats.